Number of Births and Risk of Diabetes in China's Older Women - Gu, Ying-wen; Zhang, Shuo; Wang, Jia-hao; Yang, Hua-lei; Zhang, Si-qing; Yao, Yi-dan; Wu, Yuan-yang; Xie, Lin; Li, Zhi-yun; Cao, Jin-yan (Frontiers in Medicine, 2022)
As an important life event in individuals' life, childbirth will affect the health of women to different degrees. More and more attention has been paid to whether the number of births will affect the incident diabetes in elderly women, but there are few related studies. Based on the data of the Chinese Longitudinal Healthy Longevity Survey in 2018, 6,159 older women are selected as the study population. Logistic regression analyses are used to estimate the relationship between the number of births and diabetes risk. For each additional birth, the odds ratio of maternal diabetes will decrease by 6.9% and the result is significant at the 1% level, especially among mothers having four children or less. The conclusion is equally applicable in the sample of fathers and urban mothers, but the increase in the number of births will increase the risk of diabetes in rural mothers, although this result is not statistically significant. Later age at first birth, later age at last birth, the longer childbearing period, and birth interval will significantly reduce the risk of diabetes.